Pengaruh E-wom dan Brand Reputation Terhadap Kepuasan Tamu Menginap di Harris Resort Barelang Batam - Hikmal akbar; Rian Surenda; Fran Serano Andres; Pasaribu Pasaribu (Departemen Pariwisata Universitas Negeri Padang, 2026)
The impact of brand reputation (X2) and electronic word-of-mouth (X1) on guest satisfaction (Y) at HARRIS Resort Barelang Batam is the main topic of this study. It uses a causal-associative method in a quantitative descriptive design. One hundred respondents who have visited the hotel at least twice make up the sample. Electronic word-of-mouth (X1) is classified as